Depression in patients with ankylosing spondylitis. Issue 2 (24th April 2022) - Ma, Tianjiao; Geng, Yingying; Li, Ping
Abstract: Ankylosing spondylitis (AS) is a chronic inflammatory spondyloarthropathy that can cause severe physical and functional damage. The risk of depression is higher in AS patients than in the general population. Depression in AS patients affects disease prognosis and is receiving greater attention. By mining the literature on depression in AS patients in China and other countries, we analyzed research gaps and flaws in this area. In this review, we describe current knowledge regarding depression status, pathogenesis, disease relevance, and treatment of depression in AS patients. The findings may help to prevent depression, improve treatment, and enhance chronic disease management in AS patients. Key points: The risk of depression is higher in ankylosing spondylitis (AS) patients than in the general population. Depressive symptoms in AS patients may be caused by the psychological stress, physical damage associated, and immune inflammation. Treatment with cytokine inhibitors (including tumor necrosis factor‐α, interleukin‐17, and Janus kinase inhibitors) can improve clinical depression symptoms.